El impacto de las fusiones y adquisiciones en la distribución del ingreso y el pib: América Latina, 1990-2014 - Germán Alarco Tosoni (Investigación Económica, 2019)
– The paper reviews the factors accounting for Mergers and Acquisitions (M&As). It then discusses the evolution of M&A trades, their relative importance and the economic sectors that have been influenced by M&As in sixteen Latin-American economies during 1990-2014. An integral model is developed with the aim of assessing both the impact of M&As on Gross Domestic Product (GDP) and the link between the value of M&A transactions and profits so as to determine the effects of profit share changes on private consumption, private investment and exports. The conclusion is reached that the elasticity of GDP with respect to the value of M&As is negative in countries such as Chile, Peru and Mexico. A larger value of M&As tend to redistribute income towards profits and impart a negative impact on output. The impact for other Latin American economies in our sample is either slightly positive or uncertain.
Keywords: D33; E12; G34; O54; 330; Mergers and acquisitions; Latin America; macroeconomic impacts